Investigating the Effectiveness of Compassion-Focused Therapy on Caregiver Burden and Psychological Flexibility in Caregivers of Elderly With Alzheimer Disease - Seyed Farzan Madani; Pegah Farokhzad (Sālmand)
Objectives This study aims to determine the effectiveness of compassion-focused therapy on caregiver burden and psychological flexibility in caregivers of elderly individuals with Alzheimer disease (AD). Methods & Materials The semi-experimental research method and the statistical population consisted of caregivers of elderly patients with AD referred to neurology clinics in Tehran, Iran, in the spring of 2023. A total of thirty participants were selected using the purposive sampling method and randomly assigned to two groups, namely an experimental and a control group. Subsequently, the treatment focused on compassion was implemented in an experimental group in eight 90-min sessions over 8 weeks. The second edition acceptance and action questionnaire–II (AAQ-2) and the caregiver burden inventory (CBI) questionnaire were completed as pre-test, post-test, and follow-up phases. The analysis of variance with repeated measures was used to analyze the data with SPSS software, version 23. Results Compassion-focused therapy was effective in caregiving stress and psychological flexibility in caregivers of the elderly with AD. The amount of F index for the effect of the group on lack of time, interruption in growth, physical pressure, social pressure, and emotional pressure was 12.64, 19.23, 19.06, 21.26, and 27.06, respectively. Also, the F index related to psychological flexibility was equal to 19.28. The significance level of all cases was less than 0.05, and the effect size was greater than 0.4. Conclusion It is recommended for clinical and health psychologists to support the caregiver’s family in their role and improve their mental health in the above cases through intervention programs based on treatment focused on compassion so that by improving mental health, they can be more efficient in the treatment process of elderly patients with the AD.